Perlis government gazette jilid 7-9 & Supplement 1964-1966 (Kuala Lumpur : [s.n.], 1972)
Mengandungi perlantikan; jawatan kosong; deposit yang tidak dituntut; pengurniaan pingat; tender;'Land Acquisition Act';'Criminal Procedure Code';'Elections Ordinance';'Irrigation areas Ordce';'Land Enactment':'Local Government Election Act';'Sale of food and drugs Ordinance';'Council of Regligion and Malay Customs Enactment';'Perlis Padi planters board Enactment'; dll.